PENGGUNAAN MEDIA KARTU HURUF UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS 1PADA TEMA 1 SUBTEMA 1 PEMBELAJARAN 4DI UPTD SD INPRES MAPOLI - Maxsel Koro; Karus M. Margareta; Maria Magdalena Kapek Maran (Journal of Character and ELementary Education, 2022)
This research was conducted with the aim of improving the initial reading ability of the first graders of SD Inpres Mapoli. This type of research is CAR which is carried out with the stages of planning, implementing, observing, and reflecting with the research subjects being grade 1 students, totaling 15 people. Data collection in this study was carried out using observation and test techniques, then the data obtained would be processed and analyzed further using qualitative descriptive analysis techniques. Based on the pre-cycle data obtained by the researcher, there were 2 students (13.3%) completed and as many as 13 students (86.6%) did not complete, so the researcher needed to take action and get results in the first cycle as many as 6 students. (40%) completed because they can read vowels and consonants and spell syllables into words, while there are 9 students (60%) who have not finished because students are less active and lack concentration in reading vowels and consonants. Furthermore, in the second cycle, there was an increase, namely as many as 13 students (86.7%) completed, which means the teacher began to be able to overcome the deficiencies that occurred in the first cycle. However, there were still 2 students who had not finished in the second cycle, so the teacher needed to find a way to solve the problem. can overcome the shortcomings of these students with the need for cooperation with parents of students and a more approach to these students. The increase in the percentage of student learning outcomes from cycle 1 to cycle 11 is 46.7%.